Developing Disaster Mitigation Educational Media Based on Local Folktales: Interactive Books for Children in Disaster-Prone Areas - Ambarita, Alexa Celine; Aisyabilla, Fatiha Yasmin; Widiastuti, Arum; Syabiniyah, Nuranisa; Naafi'a, Muhammad Ilman (Jurnal Ilmiah WUNY, 2026)
Background: Indonesia is a disaster-prone region, yet existing disaster mitigation education media are often unengaging and lack contextual relevance for young children. Objectives: This study aimed to develop an interactive storybook entitled "Children's Disaster Mitigation Preparedness" (SiMBA), integrating local folklore with digital technology as a disaster mitigation education tool for elementary school students in grades 1–3. Method: This study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). Validation was conducted by three experts in educational psychology, disaster content, and media design. A limited field trial was carried out at SDN Bidaracina 05 Jakarta involving grades 1–3 students as research subjects. Data were analyzed using descriptive quantitative and qualitative methods. Result: Expert validation yielded an average score of 3.45 (86.45%), categorized as "Very Appropriate." Field implementation demonstrated student comprehension levels ranging from 93% to 100%, indicating that the integration of local folklore narratives (Tangkuban Perahu, Bukit Kelam, and Lake Toba) with QR Code video features effectively enhanced children's engagement and understanding of eruption, earthquake, and tsunami mitigation. Conclusion: SiMBA successfully integrates cognitive aspects, cultural values, and digital technology, and is recommended as an innovative and child-friendly disaster mitigation learning model.